Squalene Extraction by Supercritical Fluids from Traditionally Puffed Amaranthus hypochondriacus Seeds - Teresa Rosales-García; Cristian Jiménez-Martínez; Anaberta Cardador-Martínez; Sandra Teresita Martín-del Campo; Luis A. Galicia-Luna; Dario Iker Téllez-Medina; Gloria Dávila-Ortiz (Journal of Food Quality)
Extraction of squalene, a potent natural antioxidant, from puffed A. hypochondriacus seeds was performed by supercritical fluid extraction (SCFE); besides, to have a blank for comparison, extraction was performed also by Soxhlet method using organic solvents (hexane). Chemical proximal composition and seed morphology were determined in raw, puffed, and SCFE-extracted seeds. Extracts were obtained with a 500 mL capacity commercial supercritical extractor and performed between 10 and 30 MPa at 313, 323, and 333 K under constant CO2 flow of 0.18 kg CO2/h during 8 h. The squalene content was determined and the fatty acids present in the extracts were identified by GC-MS. The extract obtained by SCFE from puffed amaranth seeds reached 460 ± 28.1 g/kg squalene in oily extract at 313 K/20 MPa.